Problems facing literacy Centers in Umm Al-Rasas district in Jordan from the teachers and technical supervisors point of view - Alnaser, Abdullah Saho (Journal of Educational and Psychological Sciences, 2021)
This study aims to reveal the problems faced by the literacy centers in Umm Al-Rasas district in Jordan. The researcher utilizes the descriptive survey methodology. The study sample includes all 15 Um-Al- Rasas literacy centers teachers, and 10 technical supervisors. The basis of the study was based upon tools from previous studies. It can be said that the study tool includes (49) paragraphs covering all the problems facing the centers. The results of the study indicated that the most prominent problems facing the centers from the teachers’ point of view are the lack of material incentives provided to workers and students in the centers, the need for the curriculum and books used in the program to be developed and modernized. As for the problems from the technical supervisor’s perspective, they were represented in the need for workers in the literacy field for training courses, in addition to the lack of financial incentives provided to students. In the light of the outcomes, the researcher suggests a set of recommendations; the most significantly are reconsidering the incentives system offered to workers and learners in the literacy program, reconsidering the annual MOE’s training courses for teachers.